Production of cell wall degrading enzymes by Corynespora cassiicola in culture and infected rubber tissue - Jayasinghe C K; Fernando T H P S; Priyanka U M S (Journal of the Rubber Research Institute of Sri Lanka, 1998)
All isolates of Corynespora cassiicola used in the investigation secreted pectin lyase when grown in liquid medium with pectin as the main source of carbon. However, none of the isolates secreted polygalacturonase in the same medium. The extracts of rubber tissue inoculated and infected with C. cassiicola also showed only pectin lyase activity. When grown in liquid medium with carboxymethyl cellulose as the main source of carbon all isolates secreted cellulases viz. cellobiase and B - glucosidase with a markedly high production in C1 and C4 isolates. Infected rubber leaf tissue with C. cassiicola also had a high activity of both cellobiase and B- glucosidase. The results of this study suggest that principal pectin enzyme involved in pathogenesis of the rubber isolate of C. cassiicola is pectin lyase and in the later stages cellulolytic enzymes possibly play a major role.